Pengaruh Corporate Social Responsibility (Csr) Dan Motivasi Terhadap Kinerja Karyawan - Aldi Alfathur Rachman; Raudhatul Hikmah; Vira Anggita Sukma; Dewi Sri Woelandari Pantjolo Giningroem (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The article "Literature Review on the Influence of Leadership and Compensation on Motivation and Performance" is a scientific article that aims to develop a research hypothesis about variable interactions that will be used in future research in the field of Human Resource Management. The method used to write this literary review article is library research, which involves collecting information from online sources such as Google Scholar, Mendeley, and other academic online platforms. The results of this literature review article are: 1) Corporate social responsibility has an impact on employee performance. 2) Motivation affects employee achievement. In addition to these two exogenous variables, there are many other factors that affect the endogeneous variables of motivation and performance, such as organizational culture, job satisfaction, and workload.